Sex-Specific B Cell and Anti-Myelin Autoantibody Response After Peripheral Nerve Injury - Lee, Hee Jong; Remacle, Albert G.; Hullugundi, Swathi K.; Dolkas, Jennifer; Leung, Jake B.; Chernov, Andrei V.; Yaksh, Tony L.; Strongin, Alex Y.; Shubayev, Veronica I. (Frontiers in Cellular Neuroscience, 2022)
Immunotherapy holds promise as a nonaddictive treatment of refractory chronic pain states. Increasingly, sex is recognized to impact immune regulation of pain states, including mechanical allodynia (pain from nonpainful stimulation) that follows peripheral nerve trauma. The present study aims to assess the role of B cells in sex-specific response to peripheral nerve trauma. Using a rat model of sciatic nerve chronic constriction injury (CCI), we analyzed sex differences in: i) the release of the immunodominant neural epitopes of myelin basic protein (MBP); ii) the levels of serum IgM/IgG autoantibodies against the MBP epitopes; iii) endoneurial B cell/CD20 levels; and iv) mechanical sensitivity behavior after B cell/CD20 targeting with intravenous (IV) Rituximab (RTX) and control, immunoglobulin (IVIG), therapy. The persistent MBP epitope release in CCI nerves of both sexes was accompanied by the serum anti-MBP IgM autoantibody in female CCI rats alone. IV RTX therapy during CD20-reactive cell infiltration of nerves of both sexes reduced mechanical allodynia in females, but not in males. IVIG and vehicle treatments had no effect in either sex. These findings provide strong evidence for sexual dimorphism in B cell function after PNS trauma and autoimmune pathogenesis of neuropathic pain, potentially amenable to immunotherapeutic intervention particularly in females. A myelin-targeted serum autoantibody may serve as a biomarker of such painful states. This insight into the biological basis of sex-specific response to neuraxial injury will help personalize regenerative and analgesic therapies.